2007
DOI: 10.1109/tmtt.2007.908673
|View full text |Cite
|
Sign up to set email alerts
|

Design of Bandpass Elliptic Filters Employing Inductive Windows and Dielectric Objects

Abstract: Abstract-In this paper, we propose an alternative configuration for the design of bandpass inductive filters using transversal topologies. The structure is based on the use of a dielectric post asymmetrically placed on a cavity resonator. The input and output windows will couple energy to the TE 102 -and TE 103 -mode resonators at the same time, therefore obtaining the transversal topology. The proposed configuration is very compact, and allows to implement transmission zeros for maximum selectivity in an easy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Coupling schemes for dual-mode filters have been analyzed according to the particular structures in many papers [7][8][9][10][11][12][13][14][15]. The filters under this study consist of the classical doublet topology as shown in Fig.…”
Section: Coupling Scheme Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Coupling schemes for dual-mode filters have been analyzed according to the particular structures in many papers [7][8][9][10][11][12][13][14][15]. The filters under this study consist of the classical doublet topology as shown in Fig.…”
Section: Coupling Scheme Analysismentioning
confidence: 99%
“…2(a). This structure is known to have a response with one transmission zero if no source to load coupling is considered [13]. The coupling matrix for this doublet is shown in Fig.…”
Section: Coupling Scheme Analysismentioning
confidence: 99%
See 3 more Smart Citations